(3bWQ Gdhdi Ydi MOjK Gdhdis - (3, eMeO Hf Ydj Hf eMeO Hf YHO Gddg, CHh YHO Gddg GdThcGfj , J (B1250 (3g` s
(3ChdgG (B:s
(3hHYO aEfg deG cGf MOjK ef YGO Edi hdjkG bO GTJed Ydi ahGFO cKjQI GdfaY LdjdI GdbO def agegG CMHHJ Cf CaQO gPG GdMOjK GdLdjd deDda eSJbd s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde(B( (3ef eGJ hgh jQi ef GdcHQ hGdNdhd hGdOjf ONd GdLfI (B) (3hEdi gfG GfJgi GdTQM ddMOjK GdbOSi s
(3GdfSNI HgG MhGTs
(3HBNQg eWGdYGJ YOjOIs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs